Surgical management of colonic perforation due to ulcerative colitis: report of a case - Mitra, Dipankar S.; Kumar, Birbal; Gupta, Balkishan (International Surgery Journal, 2023)
Surgical treatment of ulcerative colitis (UC) is indicated electively in failure of medical therapy and development of malignancy and dysplasia in long standing cases and acutely in fulminant colitis, perforation, bleeding, obstruction or in toxic megacolon. The surgical procedure in the past used to be total proctocolectomy with permanent ileostomy with its attendant psychological, social, physical, and sexual problems. With the advent of ileal pouch–anal anastomosis (IPAA) patients with UC can have a good quality of life without fear of having the permanent ileostomy. The advancement of minimally access surgery has added a new wing to the surgical armamentarium in coping the postoperative recovery, body image, sexual dysfunction etc. Laparoscopic surgery appeals to patients undergoing IPAA because they are generally young and hope to gain the potential benefit of reduced disability, more rapid recovery, and a better body image as a result of more cosmetic incisions. Depending upon the clinical presentation patient may require two or three stage procedure.